So Much Wasted Hunger, Performance, and the Morbidity of Resistance - Anderson, Patrick (Perverse Modernities: A Series Edited by Jack Halberstam and Lisa Lowe, 2010)
In So Much Wasted, Patrick Anderson analyzes self-starvation as a significant mode of staging political arguments across the institutional domains of the clinic, the gallery, and the prison. Homing in on those who starve themselves for various reasons and the cultural and political contexts in which they do so, he examines the diagnostic history of anorexia nervosa, fasts staged by artists including Ana Mendieta and Marina Abramović, and a hunger strike initiated by Turkish prisoners. Anderson explores what it means for the clinic, the gallery, and the prison when one performs a refusal to consume as a strategy of negation or resistance, and the ways that self-starvation, as a project of refusal aimed, however unconsciously, toward death, produces violence, suffering, disappearance, and loss differently from other practices. Drawing on the work of Martin Heidegger, Sigmund Freud, Giorgio Agamben, Peggy Phelan, and others, he considers how the subject of self-starvation is refigured in relation to larger institutional and ideological drives, including those of the state. The ontological significance of performance as disappearance constitutes what Anderson calls the "politics of morbidity," the embodied, interventional embrace of mortality and disappearance not as destructive, but rather as radically productive stagings of subject formations in which subjectivity and objecthood, presence and absence, and life and death are intertwined